A P2P Electricity-Carbon Trading Mechanism for Distributed Prosumers Based on Carbon Emission Flow Model - ZHAN Bochun, FENG Changsen, WANG Xiaohui, ZHANG Heng, MA Junwei, WEN Fushuan (Shanghai Jiaotong Daxue xuebao)
It is necessary to consider the carbon emission trading between prosumers when designing a distributed transaction mechanism in a distribution system. In this paper, a peer-to-peer (P2P) electricity-carbon transaction mechanism considering the carbon footprint of electricity trading is established. First, the carbon emission characteristic of energy storage system is analyzed, and a carbon emission flow model considering energy storage system is established. Next, a P2P electricity-carbon transaction model based on the carbon emission flow model is established. Based on the improved Benders decomposition method, the original problem is decomposed into the main problem considering network constraints and the subproblem of optimal scheduling for prosumers. Through distributed solutions, the optimal P2P electricity-carbon trading amount of prosumers is solved to protect the privacy of prosumers. Then, a P2P electricity-carbon trading settlement model based on the Nash bargaining model is established, and the cooperation benefit is distributed according to the contribution of prosumers in the electricity-carbon transaction. Finally, the effectiveness of the proposed model is validated by case studies on the improved IEEE 33-bus distribution system. The proposed model can not only ensure the secure operation of the distribution system, but also promote the reduction of demand-side carbon emission and fairly distribute the benefit among cooperative prosumers.